Bahasa Inggris - Ambadar, Alleyda Maharani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
This research examines Taylor Swift’s concert documentary movie called The Eras Tour (2023) that created a shift in audience’s cinema experience by not customarily watching a movie but emerge themselves which resulting in a ‘concert-feel- like’ activity. This study shows an alternative and complement live performance and streaming technology that previously researched by Scherzinger (2019) as music distribution method. Using Hjarvard’s concept of mediatization and Harvey’s theory of the production of space, I analyze how this movie concert influences audience interactions which create a new social space within cinema. Data were collected through interviews and social media documentation to examine the watching experience of The Eras Tour (2023) movie. This research finds that this mediatized concert acts as an incomplete substitution for live performances, positioning cinema as a concert space due to the implications of mediatization. Additionally, the research reveals that audience interactions beyond merely watching the movie demonstrate an amalgamation process that fosters solidarity within the fandom. Interestingly, this phenomenon generally ‘breaks the rules’ of traditional cinema logic due to the amalgamations that occur. Thus, this research shows that the mediatized concert acts as an incomplete substitution of live performance, which contribute to modern practice of mediatization in media and music industry.